Monitoring perceived stress and recovery in relation to cycling performance in female athletes - Otter, R. T. A.; Brink, M. S.; van der Does, H. T. D.; Lemmink, K. A. P. M. (International Journal of Sports Medicine, 2016)
The purpose was to investigate perceived stress and recovery related to cycling performance of female athletes over one full year. 20 female athletes (age, 27±8 years; VO2max, 50.3±4.6?mL·kg-1·min-1) were measured 8 times in one year to determine perceived stress and recovery (RESTQ-Sport) in relation to cycling performance (Lamberts and Lambert Submaximal Cycle Test (LSCT)). All 19 RESTQ-Sport scales were calculated and scores of the 4 main categories were determined (i. e., general stress, general recovery, sport-specific stress and sport-specific recovery). A balance score of total stress and recovery was calculated by recovery-stress. Power at the second stage (P80), third stage (P90) and heart rate recovery (HRR60?s) of the LSCT were determined as performance parameters. 110 RESTQ-Sports and LSCTs were analysed using a multilevel approach (random intercepts model). Higher self-efficacy was related to improvement of all performance parameters. Higher total recovery stress, and lower emotional stress were related to improvement of P90 and HRR60?s. Higher sport-specific recovery was related to P80, higher general stress, fatigue and physical complaints were related to decreased P90 and higher social stress and injury were related to decreased HRR60 s. Improved perceived recovery and stress contributed to an improved performance. Relevant information could be provided by monitoring changes in perceived stress and recovery of female athletes.